2020
DOI: 10.13057/biodiv/d211025
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of Aedes aegypti and Aedes albopictus larvae habitat in coastal areas of South Sulawesi, Indonesia

Abstract: Abstract. Ratnasari A, Jabal AR, Rahma N, Rahmi SN, Karmila M, Wahid I, 2020. The ecology of Aedes aegypti and Aedes albopictus larvae habitat in coastal areas of South Sulawesi, Indonesia. Biodiversitas 21: 4648-4654. Aedes aegypti and Aedes albopictus are arbovirus vectors that can adapt to various environmental conditions. This study aimed to analyze the spatial distribution, habitat characteristics, and the correlation between the number of Ae. aegypti and Ae. albopictus larvae with physical factors. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(38 reference statements)
0
7
0
5
Order By: Relevance
“…A study in Nepal during 2011 -2012 period revealed that each degree rise in mean temperature has shown an increase in Ae aegypti and Ae albopictus abundance (Dhimal et al, 2015). This was supported by a study in Indonesia in 2019 which revealed that there is a positive correlation between temperature and Ae aegypti and Ae albopictus larvae (Ratnasari et al, 2020). However, another study has proven that each degree rise in mean temperature by one degree Celsius was associated with a decrease in the mean Ae aegypti and Ae albopictus mosquito number by 6.49 (95%CI: -12.4 -0.58; p= 0.032) (Paul et al, 2018).…”
Section: Impact Of Temperature On Mosquito Related Indicesmentioning
confidence: 86%
“…A study in Nepal during 2011 -2012 period revealed that each degree rise in mean temperature has shown an increase in Ae aegypti and Ae albopictus abundance (Dhimal et al, 2015). This was supported by a study in Indonesia in 2019 which revealed that there is a positive correlation between temperature and Ae aegypti and Ae albopictus larvae (Ratnasari et al, 2020). However, another study has proven that each degree rise in mean temperature by one degree Celsius was associated with a decrease in the mean Ae aegypti and Ae albopictus mosquito number by 6.49 (95%CI: -12.4 -0.58; p= 0.032) (Paul et al, 2018).…”
Section: Impact Of Temperature On Mosquito Related Indicesmentioning
confidence: 86%
“…arabiensis and An . subpictus , are prevalent in ponds, swamps, and irrigation ditches with similar oxygen sources (Muturi et al 2008, Ratnasari et al 2020). This corroborates with the results of an experiment by Yamada et al (2020) where they quantified the role of oxygen depletion on an Ae .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, as one of the most productive breeding sites, Ae. aegypti thrives in used boats in Kurri Caddi (South Sulawesi) [ 21 ]. In addition, clusters of containers, which serve as “hot spots,” influence mosquito production and act as a source of infestation in the surrounding vicinity.…”
Section: Environmental Methodsmentioning
confidence: 99%